Les lettres et l’Esprit de la réforme des universités. Le point de vue des enseignants de province sur la transformation des curricula (1964) - Anthéa Chenini (Recherches en Éducation)
While they marked the end of the era of classical humanities and the scientific paradigm's domination over all educational structures, the new faculties of Letters and Humanities (1958) constitute a blind spot in the works on the reform mobilizations preceding the Faure Act (1968). This article makes visible the point of view of their teachers, focusing on the province, a category long marginalized in social science research on universities.